Resúmenes de Tesis 1987 - Autores, Varios (1987)
Resúmenes de las tesis presentadas en la Sección Química de la PUCP en el año 1987. Tesistas: Majid Taghiof, Carmen Álvarez Agüero, Helena Maruenda Castillo, Juan Rivera Orbegozo, Susana de la Torre Puente, Eduardo Espejo Merino, María Rosaura Arévalo Vega